EFFECTIVENESS OF DECOY WATER TREATMENT ON REACTIVATORS AT PT GOODYEAR INDONESIA Tbk - Sri Murda Niati; Guruh Akbar; Gemala Cahya (UPT Publication and Journal Management, Islamic University of Kalimantan, 2023)
PT Goodyear Indonesia Tbk is a tire manufacturing industry whose main need is the provision of water for steam boiler decoys. This water is obtained from groundwater and surface water such as river water which is then treated in a reactivator using one of the coagulants, namely PAC, so that impurities from river water can be removed, so the water is cleaner and can be used for steam boilers and does not interfere with a further decoy water treatment. This study aims to determine the effectiveness of water treatment in reactivators to be a reference for further treatment considerations at PT Goodyear Indonesia Tbk. The test result data showed the efficiency value between the inlet and outlet and compared it with the control limit set by the company. The efficiency test parameters consist of pH, conductivity, clarity measurement, and color measurement. Based on the results of efficiency calculations, several test parameters show that water treatment in reactivators at PT Goodyear Indonesia Tbk is still good and has a high-efficiency value.